The Girl With Rapunzel Syndrome - S, Norly; I, Nor Saadah; P, Ros’aini (IIUM Medical Journal Malaysia, 2015)
Rapunzel syndrome is a syndrome whereby a gastric trichobezoar (hair ball) extends through the pylorus, in the form of a long tail, to cause gastric outlet obstruction. It was first described by Vaughan et al. in 1968. The syndrome is mostly seen in young females with psychiatric illness. Presentations can be non-specific especially in the early stages. If left untreated it may leads to severe complications, which may include gastric ulceration, intestinal obstruction, perforated viscus and obstructive jaundice. Treatment is essentially surgical and psychiatric consultation is necessary to prevent relapses. We present the case of a 26-year-old mentally subnormal lady with gastric trichobezoar and provide a review of the literature.